ANALYSIS OF STUDENTS’ COURSEBOOK “THINK GLOBALLY ACT LOCALLY” APPLIED AT THIRD GRADE OF SMP NEGERI 9 AMBON BASED ON CUNNINGSWORTH’S CRITERIA - Solong, Alicia; Tupalessy, Pricilia; Afiliani, Afiliani; Hanayanti, Hanayanti (Pattimura University, 2024)
One of the key components to assist the teacher and students’ teaching and learning activities in the classroom is the English coursebook. As a result, it is essential to select the appropriate course book to be used. Cunningsworth's criteria is one of several criteria that can be used to identify the appropriate course book. As a result, the objective of this research is to determine how relevant the English course book